A spline collocation approach for a generalized wave equation subject to non-local conservation condition - Khuri, S.A.; Sayfy, A. (Applied mathematics and computation, 2010)
In the present paper, a collocation finite element approach based on cubic splines is presented for the numerical solution of a generalized wave equation subject to non-local conservation condition. The efficiency, accuracy and stability of the method are assessed by applying it to a number of test problems. The results are compared with the existing closed-form solutions; the scheme demonstrates that the numerical outcomes are reliable and quite accurate when contrasted with the analytical solutions and an existing numerical method.